1998
DOI: 10.1136/jnnp.64.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant pure spastic paraplegia: a clinical, paraclinical, and genetic study

Abstract: Objectives-At least three clinically indistinguishable but genetically diVerent types of autosomal dominant pure spastic paraplegia (ADPSP) have been described. In this study the clinical, genetic, neurophysiological, and MRI characteristics of ADPSP were investigated. Methods-Sixty three at risk members from five families were clinically evaluated. A diagnostic index was constructed for the study. Microsatellite genotypes were determined for chromosomes 2p, 14q, and 15q markers and multipoint linkage analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
3
45
1
Order By: Relevance
“…However, they did speculate that the atrophy is predominantly secondary to the degeneration of the descending pyramidal tract, resulting in marked atrophy at the thoracic and not at the cervical level. 4 Mild atrophy of the cervical and thoracic spinal cord (not quantified) was also reported by Durr et al, 3 Lesca et al, 5 Nicolau et al, 10 and Nielsen et al 35 In our study, patient 1 had mild atrophy of the cervical spinal cord and 2 patients of family II presented an unusual finding, namely the round T2 high signal intensity in the posterior aspect of the spinal cord representing either an enlarged and posteriorly displaced ependymal canal or a direct high signal intensity along the dorsal columns of the cord (Fig 3A, -B); in both cases, it reflects the neuropathologic finding of degeneration and atrophy of the dorsal columns of the spinal cord. Although this finding is not very conclusive in confirming the diagnosis of HSP, it may be useful in the evaluation of dorsal column degeneration.…”
Section: Discussionsupporting
confidence: 57%
“…However, they did speculate that the atrophy is predominantly secondary to the degeneration of the descending pyramidal tract, resulting in marked atrophy at the thoracic and not at the cervical level. 4 Mild atrophy of the cervical and thoracic spinal cord (not quantified) was also reported by Durr et al, 3 Lesca et al, 5 Nicolau et al, 10 and Nielsen et al 35 In our study, patient 1 had mild atrophy of the cervical spinal cord and 2 patients of family II presented an unusual finding, namely the round T2 high signal intensity in the posterior aspect of the spinal cord representing either an enlarged and posteriorly displaced ependymal canal or a direct high signal intensity along the dorsal columns of the cord (Fig 3A, -B); in both cases, it reflects the neuropathologic finding of degeneration and atrophy of the dorsal columns of the spinal cord. Although this finding is not very conclusive in confirming the diagnosis of HSP, it may be useful in the evaluation of dorsal column degeneration.…”
Section: Discussionsupporting
confidence: 57%
“…The most frequent abnormality on magnetic resonance imaging (MRI) is spinal cord atrophy, particularly in the cervical and thoracic regions. Quantitative MRI investigations have suggested that the corpus callosum may be smaller than normal [8,12,23,24]. Several MRI studies have identified a trend for white matter lesions to be more common than in controls, although individually none of these studies has found this statistically significant [23,24].…”
Section: Differential Diagnosis and Investigationsmentioning
confidence: 99%
“…Quantitative MRI investigations have suggested that the corpus callosum may be smaller than normal [8,12,23,24]. Several MRI studies have identified a trend for white matter lesions to be more common than in controls, although individually none of these studies has found this statistically significant [23,24]. Peripheral nerve conduction studies are almost always normal [4, 24,25].…”
Section: Differential Diagnosis and Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The results of electrophysiological investigations vary between studies and have not contributed significantly to the elucidation of possible differences in the aetiology and pathogenesis of the disorder. TMS studies have demonstrated that CMCTs to lower extremities are delayed in most but not all patients [7][8][9][10] ; CMCTs to upper extremities are usually normal but may be prolonged in a minority of patients, 8 11 and intracortical facilitation may be increased. 12 In none of these studies, electrophysiological findings have been combined with genotypes.…”
Section: Discussionmentioning
confidence: 99%